Association of functional variants in miRNA genes with the risk of coronary heart disease - Taqweem Ul Haq; Muhammad Riaz Khan; Sajjad Ali; Tariq Aziz; Thamer H. Albekairi; Aftab Ali Shah (Egyptian Journal of Medical Human Genetics)
Abstract Background Cardiovascular diseases, especially coronary heart disease (CHD), are currently the leading cause of mortality and morbidity. Environmental and genetic factors contribute to the pathophysiology of CHD. In this study, we investigated the associations of miRNA genes MIR222, MIR423, MIR4274, and MIR3117 with the pathogenesis of CHD. Methods Genetic inheritance models were applied to explore the association between these miRNA genes and CHD. Tetra-Primer Amplification Refractory Mutation System-Polymerase Chain Reaction (T-ARMS-PCR) was used for genotyping, and Sanger sequencing was applied for validation in selected cases. Results The codominant [χ2 = 8.058, 2; P value = 0.0178], and recessive (CC vs GC + GG) [OR = 0.4535 (0.2439–0.8669); P value = 0.0187] models demonstrated a statistically significant association between MIR222 (rs2858060) and CHD. Similarly, the co-dominant [χ2 = 6.105, 2, 2; P value = 0.0472], and additive [OR = 1.494 (1.024–2.211); P value = 0.0428] models revealed a significant association (P value < 0.05) between MIR423 (rs6505162) and CHD. In MIR4242, a novel triplet insertion (CAC) was identified exclusively in CHD samples, predicated to disrupt the stem-loop structure ofmiR-4274. However, MIR3117 showed no association with CHD, as confirmed by Sanger sequencing of 40 samples. Conclusion Our findings suggest that functional variants rs2858060, rs6505162, and a novel triplet insertion (CAC) in MIR222, MIR423, and MIR4274 respectively are strongly associated with CHD. These results underline the potential of miRNA gene variants as genetic biomarkers for CHD susceptibility.